2020
DOI: 10.1212/wnl.0000000000010577
|View full text |Cite|
|
Sign up to set email alerts
|

Acute symptomatic seizures in cerebral venous thrombosis

Abstract: ObjectiveTo identify characteristics, predictors, and outcomes of acute symptomatic seizures (ASS) in cerebral venous thrombosis (CVT), we investigated 1,281 consecutive adult patients with CVT included from 12 hospitals within the International CVT Consortium.MethodsWe defined ASS as any seizure between symptom onset and 7 days after diagnosis of CVT. We stratified ASS into pre-diagnosis and solely post-diagnosis ASS. Status epilepticus (SE) was also analyzed separately. We analyzed predictors for ASS, and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 32 publications
(44 reference statements)
5
32
1
5
Order By: Relevance
“…Also noteworthy is that a recent study has confirmed the involvement of CCVT in the venous infarctions and seizures. 28 This result was in accordance with the conclusions in our study, as cerebral parenchymal lesions, including ischemia and hemorrhage, along with seizure attacks were more prevailing in the IJVS-CVT group, despite no statistical significance.…”
Section: Thrombus Distribution In Cvt and Ijvs-cvtsupporting
confidence: 92%
“…Also noteworthy is that a recent study has confirmed the involvement of CCVT in the venous infarctions and seizures. 28 This result was in accordance with the conclusions in our study, as cerebral parenchymal lesions, including ischemia and hemorrhage, along with seizure attacks were more prevailing in the IJVS-CVT group, despite no statistical significance.…”
Section: Thrombus Distribution In Cvt and Ijvs-cvtsupporting
confidence: 92%
“…Patients were recruited from eight hospital-based consecutive adult CVT registries within the International CVT Consortium [21]. Due to the particularly rare combination of CVT and dAVF, we centrally reviewed all patients with suspected CVT and dAVF within the consortium and discovered five additional patients with suspected CVT and dAVF that did not originate from consecutive CVT registries; the University of Virginia Health System (n = 4, Charlottesville, VA, United States) and the John Hunter Hospital (n = 1, Newcastle, Australia).…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…One recent prospective international study of 1281 individuals found a 34% rate of acute symptomatic seizures, 6% of whom had status epilepticus. Neuroimaging findings associated with acute seizures included intracerebral haemorrhage, non-haemorrhagic lesions, cortical vein or sagittal sinus thrombosis and subarachnoid haemorrhage [46].…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%